The fabric of cities : aspects of urbanism, urban topography and society in Mesopotamia, Greece, and Rome - May, Natalie N.; Steinert, Ulrike. (Culture and History of the Ancient Near East, 2013)
The Fabric of Cities presents an interdisciplinary collection of articles on urbanism in ancient Mesopotamia, Israel, Greece and Rome, which focuses on the social dimension of cities' topographical features. The contributions of this book offer investigations of neighbourhoods, city gates, streets, temples and palaces drawing on textual and archaeological sources as well as art. The topics treated in this work encompass the diverse functions of public and marginal spaces in Mesopotamian cities and Rome, the role of agency in the development of Babylonian neighbourhoods, the relationship between public and private in Assyrian palaces, the connection between political strategies and temple building in Sumerian literary texts, and the communicative uses of language in Classical Greek texts to talk about urban space.